A modified animal-free serum technique for efficient isolation and proliferation of mesenchymal stem cells from Hoffa fat pad: A modified technique for isolation of mesenchymal stem cells from Hoffa fat - Olivos Meza, Anell; Cárdenas-Soria, Víctor Hugo; Luna Angulo, Alexandra Berenice; Aguilar Gaytán, Rocío; Martinez-Flores, Karina; Zamudio-Cuevas, Yessica; Landa-Solís, Carlos (Cellular and Molecular Biology, 2023)
We focus on this study in designing an alternative technique for obtaining mesenchymal stem cells (MSCs) from residual tissue, Hoffa fat, in arthroscopic procedures. Two males and two females were included, and underwent knee arthroscopy; a sample of infrapatellar adipose tissue was obtained with basket forceps. The primary culture was made using the explant method and the culture media: DMEM-high glucose, supplemented with 10% of inactivated human allogeneic serum. All the cellular cultures remained under culture conditions for three weeks, after that by flow cytometry the cells were characterized by MSCs antibody panel: CD105, CD73 and CD90. Subsequently, in the first pass, the MSCs were cultured in commercial human chondrogenic, osteogenic and adipogenic mediums, respectively. After primary culture, we obtained on average 95,600.00 ± 7,233.26 cells/cm2, and the duplication time of MSCs isolate from Hoffa fat pad was established in 39 hours. By flow cytometry, we found that surface markers percentage for expanded MSCs (CD105, CD73, CD90) in primary culture significantly increased and its morphology was fibroblastic-like. After differentiation culture which was made in the first pass, by immunofluorescence, we obtained positive cell markers for three lineages of differentiation, adipocytes: LPL protein, osteocytes: RUNX2, Osteopontin, chondrocytes: SOX9, Aggrecan and COL2A1. We managed to isolate a significant number of MSCs from this source using an easy method to implement and minimal nutrient supplementation, with high potential for differentiation to mature mesenchymal tissues and potential use in basic experimental, preclinical and even clinical research.